Analysis of DNA Polymorphism in SRY Gene of Madura Cattle Populations - , Tety Hartatik ([Yogyakarta] : Elsevier, 2014)
The aim of this research was to assess the SRY-gene polymorphism in Madura cattle populations and the hybrids of Madura cow with Limousin bull. We investigated the specific markers of the paternally transmitted Y-chromosome for the direct detection of male-mediated introgression. We performed polymerase chain reaction and restriction fragment length polymorphisme (PCR&ndash